2011
DOI: 10.1007/s00221-011-2586-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation of the angular vestibulo-ocular reflex (aVOR) after semicircular canal plugging and canal nerve section

Abstract: We investigated spatial responses of the aVOR to small and large accelerations in six canal-plugged and lateral canal nerve-sectioned monkeys. The aim was to determine whether there was spatial adaptation after partial and complete loss of all inputs in a canal plane. Impulses of torques generated head thrusts of ≈3,000°/s2. Smaller accelerations of ≈300°/s2 initiated the steps of velocity (60°/s). Animals were rotated about a spatial vertical axis while upright (0°) or statically tilted fore-aft up to ±90°. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…The model predicts that the aVOR gain in upright or in statically tilted forward or backward positions would be the same after gain adaptation in the side-down position. Indeed, this was observed experimentally for horizontal and vertical aVOR regardless of whether the aVOR gain was increased or decreased (Yakushin et al 2003a(Yakushin et al , 2003c(Yakushin et al , 2005b.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…The model predicts that the aVOR gain in upright or in statically tilted forward or backward positions would be the same after gain adaptation in the side-down position. Indeed, this was observed experimentally for horizontal and vertical aVOR regardless of whether the aVOR gain was increased or decreased (Yakushin et al 2003a(Yakushin et al , 2003c(Yakushin et al , 2005b.…”
mentioning
confidence: 61%
“…1E). Previous experiments on yaw and pitch aVOR gain adaptation indicated that the spatial phase ␤, or the head orientation in which maximal gain changes were observed, is close to the position of adaptation (Yakushin et al 2003b(Yakushin et al , 2003c(Yakushin et al , 2005a(Yakushin et al , 2005b. Because a major purpose of this study was to determine the amount of gravitydependent and -independent gain changes as a function of frequency, it was assumed that the peak gain changes occurred in the position of adaptation in this study.…”
Section: Experiments Performed On Two Cynomolgus Monkeys (M1 M2) Conmentioning
confidence: 95%
See 3 more Smart Citations